PENGARUH MEDIA PEMBELAJARAN INTERAKTIF TERHADAP MOTIVASI BELAJAR SISWA KELAS VII PADA MATA PELAJARAN IPS DI SMP NEGERI 1 KABILA - Marni Adam; Radia Hafid; Sudirman Sudirman; Ardiansyah Ardiansyah; Risca Marsanti Halid (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
This study aims to analyze the contribution of interactive learning media to seventh-grade students’ learning motivation in social studies at SMP Negeri 1 Kabila, Bone Bolango Regency. The study was motivated by students’ low learning motivation in social studies, as indicated by limited focus, enthusiasm, and active participation during classroom learning. In addition, studies examining the combined use of interactive PowerPoint, instructional videos, and Educaplay-based educational quizzes in seventh-grade social studies learning remain limited. This research employed a quantitative approach with an ex post facto design; therefore, the relationship examined in this study is statistical or associative rather than experimental causal. The population consisted of 200 seventh-grade students, and 67 respondents were selected using the Slovin formula and simple random sampling technique. Data were collected through questionnaires, observation, interviews, and documentation. The data were analyzed using validity and reliability tests, normality test, simple linear regression, t-test, correlation analysis, and coefficient of determination. The results show that interactive learning media had a positive and significant relationship with students’ learning motivation. The regression equation was Ŷ = 27.233 + 0.698X, with a t-value of 10.095 > t-table value of 1.997 and p < 0.001. The correlation coefficient of 0.781 indicates a strong relationship, while the coefficient of determination of 0.611 shows that interactive learning media contributed 61.1% to students’ learning motivation. Therefore, interactive learning media contributed positively to students’ learning motivation in social studies learning. ABSTRAK Penelitian ini bertujuan untuk menganalisis kontribusi media pembelajaran interaktif terhadap motivasi belajar siswa kelas VII pada mata pelajaran IPS di SMP Negeri 1 Kabila, Kabupaten Bone Bolango. Penelitian ini dilatarbelakangi oleh rendahnya motivasi belajar siswa dalam pembelajaran IPS, yang terlihat dari kurangnya fokus, antusiasme, dan partisipasi aktif selama pembelajaran. Selain itu, kajian tentang penggunaan kombinasi PowerPoint interaktif, video pembelajaran, dan kuis edukatif berbasis Educaplay dalam pembelajaran IPS kelas VII masih terbatas. Penelitian ini menggunakan pendekatan kuantitatif dengan desain ex post facto, sehingga hubungan yang dikaji bersifat statistik/asosiatif, bukan hubungan kausal eksperimental. Populasi penelitian berjumlah 200 siswa kelas VII, dengan sampel 67 responden yang ditentukan menggunakan rumus Slovin dan teknik simple random sampling. Data dikumpulkan melalui angket, observasi, wawancara, dan dokumentasi. Analisis data meliputi uji validitas, reliabilitas, normalitas, regresi linear sederhana, uji t, korelasi, dan koefisien determinasi. Hasil penelitian menunjukkan bahwa media pembelajaran interaktif berhubungan positif dan signifikan dengan motivasi belajar siswa. Persamaan regresi yang diperoleh adalah Ŷ = 27,233 + 0,698X, dengan nilai t hitung 10,095 > t tabel 1,997 dan p < 0,001. Nilai koefisien korelasi sebesar 0,781 menunjukkan hubungan yang kuat, sedangkan koefisien determinasi sebesar 0,611 menunjukkan bahwa media pembelajaran interaktif memberikan kontribusi sebesar 61,1% terhadap motivasi belajar siswa. Dengan demikian, media pembelajaran interaktif berkontribusi positif terhadap motivasi belajar siswa dalam pembelajaran IPS.